Long-term impact of early initiation of enzyme replacement therapy in 34 MPS VI patients: A resurvey study - Horovitz, Dafne Dain Gandelman (2021)
Declaration of Competing Interest AG, AMM, ASSP, AXA, BFFR, CML, FCS, JFSF, LCLL, LRG, TBT, JICFN: declared no conflict of interest. ACMS, ALB, CAK, DDGH, EKEAL, EMR, MCSR, MK, RCFB: received funds or reimbursement from BioMarin Brasil Farmaceutica LTDA for attending related symposia, or speaker honoraria. DDGH: received consulting fees from BioMarin Brasil Farmaceutica LTDA.